Teaching in the afterward: undoing order-words and affirming transversal alternatives. Issue 5 (3rd September 2022) - Evans, Sarah; Harrison, Michaela; Rousell, David
ABSTRACT: This paper addresses the irruptive potentiality of language in rethinking pivotal concepts in pre-service and in-service teacher education. Drawing on Deleuze and Guattari's reconceptualization of language, we undertake a radical undoing of dominant concepts of pedagogy, curriculum, and assessment as 'order-words' that variously segment, delimit, and potentialize lines of subjectification and signification in professional learning settings. We argue for a speculative and affirmative engagement with the complex trajectories of teacher education in light of this post qualitative turn, focusing on how Deleuzoguattarian concepts decouple the act of teaching from the 'teacher' as personal subject, and resituate the event of teaching within assemblages of felt transitions and vital forces. Working through vignettes that affirm transversal alternatives for exploring how teaching 'thinks' through events, we conclude by considering ways that teaching approaches the immanent outside of language, or what Deleuze simply referred to as 'a life'.